Optical properties and charge transfer effects in single-walled carbon nanotubes filled with functionalized adamantane molecules. (November 2016) - Tonkikh, A.A.; Rybkovskiy, D.V.; Orekhov, A.S.; Chernov, A.I.; Khomich, A.A.; Ewels, C.P.; Kauppinen, E.I.; Rochal, S.B.; Chuvilin, A.L.; Obraztsova, E.D.
Abstract: The filling of single-walled carbon nanotube films with 1-adamantanemethanol and 1-bromoadamantane molecules was carried out by a gas-phase procedure. Optical absorption and Raman spectroscopies revealed the effects of charge transfer for samples treated with 1-bromoadamantane. Using density functional simulations we show that the charge transfer takes place when bromine is detached from the carbon cage and accepts electrons as free-standing atoms or as polybromide structures. Transmission electron microscope images confirm the presence of individual bromine atoms inside carbon nanotubes, treated with 1-bromoadamantane molecules. The observed charge transfer is, therefore, a marker of the dehalogenization reaction, a critical step in the synthesis process of narrow 1D sp 3 nanostructures.